2012
DOI: 10.1002/jcp.24012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C treatment promotes mesenchymal stem cell sheet formation and tissue regeneration by elevating telomerase activity

Abstract: Cell sheet engineering has been developed as an alternative approach to improve mesenchymal stem cell-mediated tissue regeneration. In this study, we found that vitamin C (Vc) was capable of inducing telomerase activity in periodontal ligament stem cells (PDLSCs), leading to the up-regulated expression of extracellular matrix type I collagen, fibronectin, and integrin β1, stem cell markers Oct4, Sox2, and Nanog as well as osteogenic markers RUNX2, ALP, OCN. Under Vc treatment, PDLSCs can form cell sheet struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
197
0
34

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(236 citation statements)
references
References 42 publications
(76 reference statements)
5
197
0
34
Order By: Relevance
“…Cardiomyocytes cultured on these dishes formed a myocardial cell sheet within 4 days. (12) cultured periodontal ligament stem cells treated with vitamin C (Vc) at various concentrations. The cells form cell sheet structures at concentrations of Vc >20 µg/ml, as Vc can increase cell matrix production.…”
Section: Methods For Harvesting Cell Sheetsmentioning
confidence: 99%
“…Cardiomyocytes cultured on these dishes formed a myocardial cell sheet within 4 days. (12) cultured periodontal ligament stem cells treated with vitamin C (Vc) at various concentrations. The cells form cell sheet structures at concentrations of Vc >20 µg/ml, as Vc can increase cell matrix production.…”
Section: Methods For Harvesting Cell Sheetsmentioning
confidence: 99%
“…5 Cell sheets were recently induced using a vitamin C (Vc) inducing method because of increased cell matrix production and deposition. 6 This cell processing approach could effectively preserve …”
Section: Introductionmentioning
confidence: 99%
“…The cells were cultured in medium containing Vc (20 µg/mL, Sigma-Aldrich) for 10 days until cell sheet formation, and the cell sheet was lifted using a scraper ( Figure 1B). 12 There were two kinds of cell sheets: BMP-2 gene-modified BMSC cell sheet (BMP/CS) and EGFP gene-modified BMSC cell sheet (EGFP/CS).…”
Section: Fabrication Of Gene-engineered Cell Sheetmentioning
confidence: 99%
“…10,11,32 In this study, Vc was added to create cell sheet, because of its properties of increasing cell proliferation and ECM biosynthesis. 12 Liu et al 33 also found that BMSC sheet could evidently enhance osteogenic differentiation compared with BMSCs, which because of the cell sheet enriches ECM and plays an important role in regulating the cell differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation